2010
DOI: 10.1007/s11671-010-9681-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver Colloids-Filled Photonic Crystal Arrays for Photoluminescence Enhancement

Abstract: For the improved surface plasmon-coupled photoluminescence emission, a more accessible fabrication method of a controlled nanosilver pattern array was developed by effectively filling the predefined hole array with nanosilver colloid in a UV-curable resin via direct nanoimprinting. When applied to a glass substrate for light emittance with an oxide spacer layer on top of the nanosilver pattern, hybrid emission enhancements were produced from both the localized surface plasmon resonance-coupled emission enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Fluorescence enhancement of the Au NPs in TiO 2 inverse opal photonic crystal has achieved SARS and HIV virus detection using label-free DNA, the signal intensity and the detection sensitivity is improved by one order of magnitude [ 14 ]. Park et al [ 15 ] reported the formation of photonic crystals from the resin and further enhanced the fluorescence by embedding Ag NPs. In order to further explore the new method of high sensitivity detection of the biology based on the PSi photonic devices, the combination of the unique photon transmission control capability (band-gap of Bragg reflector, defect mode of MC etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence enhancement of the Au NPs in TiO 2 inverse opal photonic crystal has achieved SARS and HIV virus detection using label-free DNA, the signal intensity and the detection sensitivity is improved by one order of magnitude [ 14 ]. Park et al [ 15 ] reported the formation of photonic crystals from the resin and further enhanced the fluorescence by embedding Ag NPs. In order to further explore the new method of high sensitivity detection of the biology based on the PSi photonic devices, the combination of the unique photon transmission control capability (band-gap of Bragg reflector, defect mode of MC etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The metasurfaces provide an avenue for realizing a new generation of flat optical elements with unique functionalities such as frequency selectivity, wavefront shaping and polarization control. Plasmonic metasurfaces with nanorods , nanoparticles , nanocolloids , nanohole arrays , half‐shell arrays , tilted nanopillars , gradient dimmers , rectangular nanoholes and hybrid plasmonic‐photonic crystals have been introduced to enhance the fluorescence intensity in large areas. Split‐ring‐resonator‐based (SRR‐based) plasmonic metasurfaces have been widely used for their fruitful electric and magnetic modes in a variety of applications such as quantum light sources , Raman spectroscopy and optical sensors .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In previous studies on surface plasmon enhanced emission of QDs, metal nanostructures have been produced by several different methods. [20][21][22][23][24] The most widely used process is electron-beam lithography, 12,13,25 which is suitable for the proof-of-concept experiments due to the high accuracy of the fabrication process, although it is very costly. Another often used process is nanosphere lithography, 14,15,18 which uses a two-dimensional array of spheres as a template for the formation of metal nanostructures.…”
Section: Introductionmentioning
confidence: 99%